2012
DOI: 10.1121/1.3676622
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional biomechanical properties of human vocal folds: Parameter optimization of a numerical model to match in vitro dynamics

Abstract: The human voice signal originates from the vibrations of the two vocal folds within the larynx. The interactions of several intrinsic laryngeal muscles adduct and shape the vocal folds to facilitate vibration in response to airflow. Three-dimensional vocal fold dynamics are extracted from in vitro hemilarynx experiments and fitted by a numerical three-dimensional-multi-mass-model (3DM) using an optimization procedure. In this work, the 3DM dynamics are optimized over 24 experimental data sets to estimate biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…However, except for numerical models, [34][35][36] a supplementary investigation of the medial surface dynamics is nearly impossible. Therefore, in this work, we performed ex-vivo experiments with three human cadaver hemilarynges.…”
Section: Introductionmentioning
confidence: 99%
“…However, except for numerical models, [34][35][36] a supplementary investigation of the medial surface dynamics is nearly impossible. Therefore, in this work, we performed ex-vivo experiments with three human cadaver hemilarynges.…”
Section: Introductionmentioning
confidence: 99%
“…The model has been extensively used for studying the physics of voice production in both normal and pathological conditions [4][5][6][7][8][9][10]. A shortcoming of this type of model is the lack of physiological correlation between tissue properties and model system parameters [11,12]. Although some effort has been made to establish these relationships [13,14], direct clinical applications are still difficult because a realistic representation of laryngeal physiology is often required in clinics.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the modulus increased linearly (Goodyer et al, 2010) from the superior aspect to the inferior aspect according to the specified VMD. Yang et al (2012) showed that all the stiffnesses (lateral, vertical, and longitudinal) have vertical variation. Thus in the current study, in each case all the three moduli (transverse Young's modulus, longitudinal Young's modulus, and longitudinal shear modulus) were varied simultaneously with the same VMD.…”
Section: Variation Of Materialsmentioning
confidence: 99%
“…This vertical stiffness variation was proposed to be important for phonation as it can promote the divergent angle during the vibration (Oren et al, 2014). Beside experimental measurements, vertical stiffness variation has also been common in spring-mass vocal fold models (see, e.g., Ishizaka and Flanagan, 1972;Story and Titze, 1995;Yang et al, 2010;Yang et al, 2012). Yang et al (2012) showed that it is essential to have this feature in order for the spring-mass models to match in vivo vocal fold kinematics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation